Association between Two Resistin Gene Polymorphisms and Metabolic Syndrome in Jilin, Northeast China: A Case-Control Study - Fu, Yingli; Yu, Yaqin; Wu, Yanhua; You, Yueyue; Zhang, Yangyu; Kou, Changgui (Disease Markers, 2017)
Metabolic syndrome (MetS) is a significant health care problem worldwide and is characterized by increased fasting glucose and obesity. Resistin is a protein hormone produced both by adipocytes and immunocompetent cells, including those residing in adipose tissue, and is believed to modulate glucose tolerance and insulin action. This study examined the association of resistin gene polymorphisms, rs1862513 and rs3745368, and related haplotypes with the development of metabolic syndrome in a Han Chinese population. This case-control study was performed on 3792 subjects, including 1771 MetS cases and 2021 healthy controls from the Jilin province of China. Metabolic syndrome was defined according to the criteria of the International Diabetes Federation (IDF). Logistic regression analysis was used to estimate the relationship between gene polymorphism and MetS. Our results showed that there were no significant associations between MetS and the genotype distributions in four kinds of inheritance models, allele frequencies, and related haplotypes of resistin gene polymorphisms rs1862513 and rs3745368 (all p values > 0.05). Based on our study findings, we concluded that mutations in resistin genes are not associated with the presence of MetS in a Han Chinese population from Jilin province in China.